Tiongkok: Analisa Balance Of Power dalam Perang Dagang antara Amerika Serikat dengan Tiongkok pada Tahun 2018 - Khakimatul Khoiriyah; Andi Akhmad Basith Dir (Journal of International Relations Diponegoro, 2020)
China became an emerging economic power whose the presence in international affairs, that cause United States as a hegemon felt its position and national security threatened. This research would explained how China effort to balance the power of United States as a hegemon which is cause trade wars between both countries on 2018. This research use neorealism theory, specifically defensive realism with balance of power concept. This research argues that Belt and Road initiative, Made in China 2025 development project, technology development as a defense strategy and geopolitical strategy are the balancing way that be done by China which trigerred trade wars with Unites States. Data is collected using literature reviews, documentation, and official government archives. The results of this study indicate that the initiation carried out by China with belt and road initiative, made in China 2025, technology development as a defense strategy and geopolitical strategy are China's effort to balance power with the United States as a hegemon, the power used by China in balancing power with the United states is combination from both forms of power between material strength (hard power) and latent power (soft power) possessed by a country, that is smart power.